2009
DOI: 10.1186/1471-2199-10-49
|View full text |Cite
|
Sign up to set email alerts
|

Breeding response of transcript profiling in developing seeds of Brassica napus

Abstract: Background: The upgrading of rapeseed cultivars has resulted in a substantial improvement in yield and quality in China over the past 30 years. With the selective pressure against fatty acid composition and oil content, high erucic acid-and low oil-content cultivars have been replaced by low erucic acid-and high oil-content cultivars. The high erucic acid cultivar Zhongyou 821 and its descendent, low erucic acid cultivar Zhongshuang 9, are representatives of two generations of the most outstanding Chinese rape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 63 publications
(70 reference statements)
3
45
0
2
Order By: Relevance
“…Moreover, in previous studies, there exist inconsistent observations regarding the temporal changes in expression levels of genes related to oil biosynthesis in B. napus . Troncoso-Ponce et al (2011) reported a decline in relative abundance of expressed sequence tags for many oil biosynthesis enzymes during seed development in B. napus , while other studies indicated a bell-shaped temporal expression pattern (Hu et al, 2009; Deng et al, 2015). More investigations are required to resolve the dispute.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, in previous studies, there exist inconsistent observations regarding the temporal changes in expression levels of genes related to oil biosynthesis in B. napus . Troncoso-Ponce et al (2011) reported a decline in relative abundance of expressed sequence tags for many oil biosynthesis enzymes during seed development in B. napus , while other studies indicated a bell-shaped temporal expression pattern (Hu et al, 2009; Deng et al, 2015). More investigations are required to resolve the dispute.…”
Section: Introductionmentioning
confidence: 96%
“…High-throughput gene expression profiling technologies, especially RNA sequencing, have been increasingly utilized to identify the key genes involved in lipid metabolism or seed development for various plants, such as soybean (Chen et al, 2012; Goettel et al, 2014), peanut (Yin et al, 2013), castor (Brown et al, 2012; Zhang et al, 2016), maize (Lu et al, 2013), Arabidopsis (Le et al, 2010; Belmonte et al, 2013), and rapeseed (Hu et al, 2009; Troncoso-Ponce et al, 2011; Chen et al, 2015; Deng et al, 2015; Xu et al, 2015). Although, considerable research has been devoted to study the molecular mechanism underlying lipid metabolism in various plants, little effort has been made to investigate, at the whole-genome level, dynamic changes of oil biosynthesis genes during seed development in B. napus , which is different from other oil plants in terms of oil content and oil composition.…”
Section: Introductionmentioning
confidence: 99%
“…The production of malonyl-CoA catalyzed by ACCase is the rate-limiting step in the process of fatty acid biosynthesis (Thelen et al, 2000;Fukuda et al, 2013). Previous studies have confirmed that heteromeric ACCase plays an important regulatory function during oil synthesis and accumulation in plant seeds (Thelen et al, 2000;Dong et al, 2004;Hu et al, 2009;Liu et al, 2009;Li et al, 2011). Homomeric ACCase is composed of a large multifunctional polypeptide (Sasaki and Nagano, 2004) and heteromeric ACCase is composed of a biotin carboxyl carrier protein (BCCP), biotin carboxylase (BC), and carboxyltransferase (CT), which consists of α-and β-subunits.…”
Section: Introductionmentioning
confidence: 98%
“…Marker segregation distortion is a common phenomenon in crops [27,46,47], especially in maps derived from DH population regardless of marker types [16,23,24,29]. This distortion probably results from gametic or zygotic selection, or from a specific selection derived from the production of plants in vitro microspore culture.…”
Section: Discussionmentioning
confidence: 99%